2014
DOI: 10.1371/journal.pone.0102213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cafeteria Diet History on Cue-, Pellet-Priming-, and Stress-Induced Reinstatement of Food Seeking in Female Rats

Abstract: BackgroundRelapse to unhealthy eating habits is a major problem in human dietary treatment. The individuals most commonly seeking dietary treatment are overweight or obese women, yet the commonly used rat reinstatement model to study relapse to palatable food seeking during dieting primarily uses normal-weight male rats. To increase the clinical relevance of the relapse to palatable food seeking model, here we pre-expose female rats to a calorically-dense cafeteria diet in the home-cage to make them overweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 71 publications
3
13
0
1
Order By: Relevance
“…We also examined whether differences in motivational state contributed to performance on devaluation tasks in lean and obese mice. Although there was no significant difference in total lever presses between lean and obese mice during the test, obese mice consistently made fewer responses throughout training, which is in keeping with reduced instrumental actions of obese rodents observed in previous reports 23,24 . The reduction in instrumental responding may be attributed to a downshift in the expected value of the reward compared to their home cage diet 23 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We also examined whether differences in motivational state contributed to performance on devaluation tasks in lean and obese mice. Although there was no significant difference in total lever presses between lean and obese mice during the test, obese mice consistently made fewer responses throughout training, which is in keeping with reduced instrumental actions of obese rodents observed in previous reports 23,24 . The reduction in instrumental responding may be attributed to a downshift in the expected value of the reward compared to their home cage diet 23 .…”
Section: Discussionsupporting
confidence: 89%
“…Although there was no significant difference in total lever presses between lean and obese mice during the test, obese mice consistently made fewer responses throughout training, which is in keeping with reduced instrumental actions of obese rodents observed in previous reports 23,24 . The reduction in instrumental responding may be attributed to a downshift in the expected value of the reward compared to their home cage diet 23 . We tried to mitigate this effect by using a higher sucrose concentration during instrumental training, 30% compared to the 9% sucrose present in the high fat diet.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, several early studies showed that exposure to an intermittent footshock stressor that reinstates drug seeking (Shaham et al, 2000a) does not reinstate food reward seeking in male rats trained to self-administer food pellets (Ahmed and Koob, 1997), sucrose pellets (Le et al, 1998;Mantsch and Goeders, 1999), or sucrose solution (Buczek et al, 1999). However, more recently, Chen et al (2014b) showed that intermittent footshock modestly reinstates palatable food (high carbohydrate pellets) seeking in female rats with a history of 'cafeteria diet' consumption during adolescence. There is also evidence that intermittent footshock stress reinstates operant responding previously reinforced by brain stimulation reward (Shalev et al, 2000); this finding is in agreement with results from an early study (Deutch and Howarth, 1962).…”
Section: Generality To Other Drug and Non-drug Rewardsmentioning
confidence: 98%
“…Numerous recently published research works -focused at understanding the role of diet in inducing obesity and metabolic syndrome-have utilized rodent models of diet-induced obesity (DIO) through the administration of cafeteria (CAF) diets [1][2][3][4][5][6][7][8][9]. The CAF-diet consists of highly palatable, energy dense and unhealthy human junk food-items -with high-salt, high-sugar, high-fat and low-fiber content.…”
Section: Introductionmentioning
confidence: 99%